Preparation of photoluminescent monolayers based on a polyoxotungstoeuropate - Sousa, FL (2004)
Here we report the synthesis of a polyoxotungstoeuropate anion that was found to have very interesting luminescence features. This compound was encapsulated with high molecular weight cations and then thin films were produced by Langmuir–Blodgett techniques. Photoluminescent studies were performed on the as prepared Eu(III) polyoxotungstate compound, on the surfactant encapsulated species, and on monolayers transferred to a quartz substrate using the Langmuir–Blodgett technique.